2020
DOI: 10.1177/2055102920959576
|View full text |Cite
|
Sign up to set email alerts
|

Sexual self-disclosure, internalized homophobia and depression symptoms among sexual minority women in Vietnam

Abstract: This study used an online survey of a sample of sexual minority Vietnamese women ( N = 302, Mean = 21.23) who self-identified as lesbian (48.7%), bisexual (42.2%), and other (8.9%). The purpose of the study was to examine the relationship among self-disclosure, internalized homophobia, and symptoms of depression. This topic has never before been studied in Vietnam. Structural equation modeling indicates that a higher level of self-disclosure with friends and coworkers leads to less self-stigmatization and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…As Elder states (Elder et al 2003), more important than the occurrence of socio-contextual changes perse is the developmental moment at which these changes occur in a person's life cycle. Thus, moments of transition and developmental adjustment in older gay and bisexual people have been constrained by the socio-cultural context with recurrent events of victimization and microaggressions that potentially hinder the sense of belonging with other sexual minorities and the connection and integration of their own sexual identity; This unfavorable context contributed to the occurrence of internalized sexual stigma, which was also observed in this study (Duc et al 2020;Frost and Meyer 2009;Huang et al 2023).…”
Section: Discussionsupporting
confidence: 52%
“…As Elder states (Elder et al 2003), more important than the occurrence of socio-contextual changes perse is the developmental moment at which these changes occur in a person's life cycle. Thus, moments of transition and developmental adjustment in older gay and bisexual people have been constrained by the socio-cultural context with recurrent events of victimization and microaggressions that potentially hinder the sense of belonging with other sexual minorities and the connection and integration of their own sexual identity; This unfavorable context contributed to the occurrence of internalized sexual stigma, which was also observed in this study (Duc et al 2020;Frost and Meyer 2009;Huang et al 2023).…”
Section: Discussionsupporting
confidence: 52%
“…Given that stressors influence one another (Meyer, 2003), experiencing everyday discrimination and not coming out can lead to the internalization of societal prejudices, which gay and lesbian individuals aim at themselves and which can, in turn, cause worse mental health. For instance, Duc et al (2020) and Pistella et al (2016) found a relationship between greater outness and lower levels of internalized sexual stigma. Overall, the pattern of associations we found is congruent with what was demonstrated in another comparative study of Italy and Spain (Baiocco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%